A Case of Heel Reconstruction with a Reverse Sural Artery Flap in a Hemophilia B Patient - Byung Kwon Lee; Jeong Su Shim (Archives of Plastic Surgery, 2012)
Hemophilia B is a rare blood coagulation disorder. Complications such as bleeding and hematoma can cause necrosis of flaps, wound disruption, and the disturbance of wound healing. In particular, guidelines for flap operations in hemophilia B patients have still not been defined, and case reports are rare. We reconstructed the heel of a 41-year-old male hemophilia B patient using a reverse sural artery flap operation. The patient presented with mild hemophilia, having 27% of the normal value of coagulation factor IX. Coagulation and the changing value of the coagulation factor were regularly measured, and 70% of the normal value of coagulation factor IX was maintained through the injection of recombinant coagulation factors and antihemorrhagics. Hematoma developed twice (postoperative day [POD] 5 and POD 7) and in each case the hematoma was removed. Injections of recombinant coagulation factors and antihemorrhagics were continuously administered until postoperative week 2. When the coagulation factors were within normal ranges. In this article, a hemophilia B patient underwent reverse sural artery flap surgery and the healing progress was analyzed. We conclude that higher than baseline levels of coagulation factors are needed for successful healing in reverse sural artery flap surgery.